2021
DOI: 10.1155/2021/5861848
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Beverages on the Color Stability of Nanocomposite Denture Base Materials

Abstract: Background. The effect of beverages on nanocomposite denture base materials is neglected. Therefore, this study aimed to investigate the influence of different beverages (coffee, tea, cola, and mineral water) on the color stability of nanoparticles-modified denture base materials (DBMs). Materials and Methods. A total of 280 specimens (n = 10/group) were prepared from heat-polymerized acrylic resin modified with different concentrations (3% and 7%) of zirconium dioxide (nano-ZrO2), titanium dioxide (nano-TiO2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…SiO 2 nanoparticles have good electrical insulation and thermal stability as well as high abrasion resistance. Azmy et al found that addition of SiO 2 nanoparticles to acrylic resin denture bases would increase color stability after being immersed in beverage solutions [ 14 ]. Tian et al found that incorporation of SiO 2 particles to composite resin significantly improved the flexural strength [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…SiO 2 nanoparticles have good electrical insulation and thermal stability as well as high abrasion resistance. Azmy et al found that addition of SiO 2 nanoparticles to acrylic resin denture bases would increase color stability after being immersed in beverage solutions [ 14 ]. Tian et al found that incorporation of SiO 2 particles to composite resin significantly improved the flexural strength [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the manufacturer's recommendations, NP/powder mixtures were added to the monomer, mixed, and then packed in dough stage in the prepared mold spaces within a metal flask. The nanocomposite specimens were prepared simulating laboratory procedures used for denture fabrication with specific dimensions as detailed in previous studies [8,33,35]. After polymerization, resin specimens were retrieved from the flask and finished using a tungsten carbide bur.…”
Section: Methodsmentioning
confidence: 99%
“…Silicon dioxide (SiO 2 ) nanoparticles have good electrical insulation and thermal stability as well as high abrasion resistance. Introduction of silicon dioxide (SiO 2 ) nanoparticles in the acrylic dental resin enhanced the color stability and translucency in the presence of beverage solution [8].…”
Section: Ceramic Nanofillersmentioning
confidence: 99%